Teaching for Transfer: Insights from theory and practices in primary-level French-second-language classrooms - Thomas, Reed; Mady, Callie (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2014)
This paper illustrates teaching for transfer across languages by synthesizing key insights from theory and previously published research alongside our case study data from primary-level teachers in core French-second-language (CF) classrooms in Ontario, Canada. Drawing on research that redefines language transfer as a resource, this study drew on several influential theoretical notions and data collected through interviews and classroom observations. All of these sources point to a multi-leveled approach to teaching for transfer that includes considerations of learning, teaching and contextual features. Study data suggest that CF teachers plan for transfer and use a range of strategies likely to promote its use with students. This paper connects theory, research and practice with the aim of strengthening dialogue among researchers and educators.